Eficacia y realidad del observatorio de familia en Colombia (2017)
This document projects demonstrate why observatories family in Colombia do not perform within the original idea that harbored in its creation.I will give a review from the scope of the definition of family for treatment that international law has set of what is proper in Colombia and as often have large contrasts within the same right to remedy and safeguard the family. On the one hand, I will highlight how these worldwide with special emphasis on Latin to lay concrete foundations did what is the reality of the observatories in Colombia.Moreover, I will demonstrate the use so far is giving these entities is not the society needs and then propose guidelines for a new observatories addressing family in Colombia; marking which is to be the process that private and public actors must continue without neglecting human rights and our constitution.